A Global Workforce: The Phenomenon of Labour Mobility in the EU with Special Reference to Cyprus - Gouliamos, Kostas; Theocharous, Antonis L. (Études helléniques / Hellenic Studies, 2008)
The present study provides a critical overview and assessment of the phenomenon of labour mobility in the EU with special reference to the microstate of Cyprus. At the same time the study provides a set of policy recommendations for curbing the problems hindering the optimization of mobility levels towards Cyprus in particular and EU in general.